Transition-metal-free, atom-economical cascade synthesis of novel 2-sulfonated-benzo[f][1, 7]naphthyridines and their cytotoxic activities. Issue 14 (5th April 2018) - Arepalli, Sateesh Kumar; Choi, Yunseon; Lee, Kiho; Kang, Jong-Soon; Jung, Jae-Kyung; Lee, Heesoon
Abstract: An efficient, transition-metal-free cascade synthetic method has been developed for new 2-aryl/heteroaryl sulfonated benzo[ f ][1, 7]naphthyridines. It is tert -butyl hydroperoxide (TBHP) mediated highly regioselective sulfonylation‒cyclization‒aromatization process between N -(3-aryl/heteroarylprop-2-yn-1-yl)quinolin-3-amines and aryl/heteroaryl sulfonylhydrazides. This synthetic protocol offers one-step strategy for CS and CC bond formations with a broad range of functional group tolerance. It is a simple, mild, and atom-economical route for the synthesis of various valuable functionalized 1, 2-aryl/heteroaryl sulfonated benzo[ f ][1, 7]naphthyridines in moderate yields. Since the core motif of 2-sulfonated benzo[ f ][1, 7]naphthyridines are biologically and pharmaceutically important (TLR activity 7, 8 modulators). Additionally, the synthesized derivatives were evaluated for their in vitro cytotoxic activities against six human cancer cell lines including lung (NCIH23), colon (HCT15), gastric (NUCG-3), renal (ACHN), prostate (PC-3), and breast (MDA-MB-231) cell lines. These compounds displayed significant cytotoxic activities against all tested human cancer cell lines. Graphical abstract: Highlights: This synthetic method is simple, mild, efficient, and atom-economic. It is a highly regioselective, transition-metal-free and cascade synthesis. It is a one-pot sulfonyl radical addition – cyclization – aromatization process. One-step strategy for CC & CS bond formations. First report on the synthesis of novel 2-aryl/heteroaryl sulfonated benzo[ f ][1, 7]naphthyridines.